2014
DOI: 10.4067/s0718-48832014000100005
|View full text |Cite
|
Sign up to set email alerts
|

Análisis De La Expresión De La Cortesía en Rtve: Internacional Para La Enseñanza Del Español-Lengua Extranjera

Abstract: RESUMENEl fenómeno de la cortesía como contenido sociocultural de la enseñanza de una lengua extranjera ha sido objeto de estudio de muchas investigaciones actuales bajo la justificación de que el desconocimiento de sus elementos y normas puede generar un choque cultural entre un aprendiz de una lengua extranjera y un nativo de la misma. En este trabajo se aborda el estudio descriptivo de este fenómeno a través de cinco series de RTVE emitidas por Internet con el objeto de ofrecer un recurso válido para la ens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Given the multiple variables that need to be taken into account when deciding which PA to use, the inherent variability in T/V use across communities of speakers, and possible mismatches between the students’ L1 and L2, research has shown that appropriately using these forms in L2 Spanish is far from easy for many learners (Marsily, 2022; Más Álvarez, 2014; Navarro Gala, 2000; Ramos-González & Rico-Martín, 2014). Consequently, researchers have called for more attention to the teaching of PAs in L2 Spanish.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given the multiple variables that need to be taken into account when deciding which PA to use, the inherent variability in T/V use across communities of speakers, and possible mismatches between the students’ L1 and L2, research has shown that appropriately using these forms in L2 Spanish is far from easy for many learners (Marsily, 2022; Más Álvarez, 2014; Navarro Gala, 2000; Ramos-González & Rico-Martín, 2014). Consequently, researchers have called for more attention to the teaching of PAs in L2 Spanish.…”
Section: Literature Reviewmentioning
confidence: 99%